Meroterpenoid Hydroquinones from Cordia globosa - Silva,Ana Karine O. (2016)
Two new meroterpenoid hydroquinones,rel-(4bE,6Z,8E,9aS,10S)-1,4-dihydroxy-9a,10-dihydro-10,12-epoxy-5-methylbenzo[a]azulen-12-one andrel-(4bZ,6Z,8E,9aS,10S)-1-hydroxy-9a,10-dihydro-4,11:10,12-diepoxy-benzo[a]azulen-11,12-dione, along with the known peptide derivative (S)-N-benzoylphenylalanine-(S)-2-benzamide-3-phenylpropyl ester, were isolated from the roots of Cordia globosa. Their structures were determined by 1D and 2D nuclear magnetic resonance (NMR) spectrometry, Fourier transform infrared (FTIR) spectroscopy and high resolution atmospheric pressure chemical ionization mass spectrometry (HRAPCIMS) data analysis. The new compounds were tested against three human cancer cell lines (colon adenocarcinoma, ovarian carcinoma and glioblastoma), but none of them exhibited any activity.